1971
DOI: 10.1063/1.1653842
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Oxidation of Fe in Permalloy Films

Abstract: On the basis of He-ion backscattering, x-ray fluorescence, and complementary measurements, it is unambiguously established for the first time that the oxide layer on the surface of oxidized 81% Ni-19% Fe evaporated films is predominantly Fe-oxide. Extrapolation of results for pure iron films indicates that the oxide is most likely antiferromagnetic α-Fe2O3. On the basis of ferromagnetic resonance measurements, it is concluded that the oxide negligibly affects the pinning of the bulk spins at the film-oxide int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Bajorek et al 25 concluded that the oxide of Permalloy is composed primarily of ␣-Fe 2 O 3 based upon He-ion backscattering and x-ray fluorescence measurements. Antiferromagnetic ordering of an intentionally grown surface oxide has been inferred from both low-temperature hysteresis measurements and ferromagnetic resonance studies.…”
Section: Discussionmentioning
confidence: 99%
“…Bajorek et al 25 concluded that the oxide of Permalloy is composed primarily of ␣-Fe 2 O 3 based upon He-ion backscattering and x-ray fluorescence measurements. Antiferromagnetic ordering of an intentionally grown surface oxide has been inferred from both low-temperature hysteresis measurements and ferromagnetic resonance studies.…”
Section: Discussionmentioning
confidence: 99%
“…We expect that the magnetic oxide formed in this experiment is most likely to be antiferromagnetic ␣-Fe 2 O 3 , which is known to form predominantly at the interface of the oxidized permalloy ͑NiFe͒ films. 16 It should be pointed that similarly, one expects to observe TMR in junctions with just one magnetic electrode and a magnetic dielectric layer. Another possible variation of this approach is to employ a junction with an antiferromagnetic electrode and ferromagnetic tunnel barrier.…”
Section: -mentioning
confidence: 99%
“…We have chosen to study the oxidation of Permalloy (Ni0.s0Fe0.2o) films using these techniques, with the intent to establish a foundation for future studies of various thin film systems. The complicated surface composition and chemistry of air-exposed Permalloy films have been studied by Pollak and Bajorek using AES and XPS (15) and the oxidation (in the 350 ~ 500~ range) of Permalloy films was carried out by Coren and Francombe (16) and by Bajorek et al (17). However, to our knowledge no kinetic data have been reported for Permalloy film oxidation.…”
mentioning
confidence: 99%